Modernization of the Pseudomonas syringae pathovars serogrouping scheme - Pasichnyk, Lidiia; Butsenko, Liudmyla (My University, 2022)
In 1979, L.T. Pastushenko and I.D. Symonovych developed a scheme of serogrouping phytopathogenic bacteria of the Pseudomonas genus, which is still used now. However, today's using this serogrouping scheme is complicated by the lack of all data accumulated over the years of its application. Moreover, the scheme does not correspond to the modern taxonomy of phytopathogenic bacteria of the Pseudomonas genus. Aim. On the basis of own experimental results and data of scientific literature, to carry out modernization of the serogrouping scheme of phytopathogenic bacteria of the Pseudomonas genus. Methods. The strains of Pseudomonas syringae pathovars such as atrofaciens, coronafaciens, tabaci, which were isolated from plants of wheat, rye, oats, tobacco, and various species of affected weeds in different regions of Ukraine have been studied in the work. Antigenic properties of bacterial strains were studied by agglutination and precipitation reactions (the Ouchterlony double immunodiffusion techniques) using antisera to P. syringae strains of nine serological groups (I, II, III, IV, V, VI, VII, VIII, IX). To carry out the precipitation reaction, O- and OH-antigens were obtained by a modified Grasse's method. The presence of the same number of precipitation lines of the studied antigens as the number of lines with homologous antiserum of the corresponding serogroup testified to their belonging to this serogroup according to the known serogrouping scheme of phytopathogenic bacteria developed in 1979 by L.T. Pastushenko and I.D. Symonovych. Results. It has been proved that strains of P. syringae pathovars isolated from different cereals (rye, wheat, oats) and segetal vegetation differ in antigenic composition. The antigenic composition of P. syringae strains depends on the host plant from which the pathogen was isolated. Strains of the causative agent of basal glume rot P. syringae pv. atrofaciens isolated from wheat belong to four serological groups (II, IV, V, VI), from rye - to five serological groups (I, II, IV, V, VI), as well as strains of this pathogen isolated from segetal vegetation of wheat agrophytocenosis. Strains of the halo bligth P. syringae pv. coronafaciens from affected oat plants belong to two serological groups (I, V). The serogrouping scheme has been supplemented by new data on the antigenic properties of P. syringae pv. tomato, the causative agent of the bacterial speck disease of tomatoes (Solanum lycopersicum), which is classified as serogroup IV. It has been found that P. syringae pv. tabaci strains, which cause wildfire of tobacco, are part of three serogroups - VII, VIII, IX, and not of two ones, as was presented in the known scheme (1979). Conclusions. Therefore, on the basis of our own research and literature data, the serogrouping scheme of phytopathogenic bacteria of the Pseudomonas genus developed by L.T. Pastushenko and I.D. Symonovych has been modernized. In the renovated scheme, current species' names of phytopathogens are present, this scheme introduces new information about the serogroups of P. syringae pv. atrofaciens isolated from rye seeds and plants, weeds, P. syringae pv. coronafaciens - from oat plants, P. syringae pv. tabaci - from tobacco, and P. syringae pv. tomato - from affected tomato plants.

У 1979 році Л.Т. Пастушенко та І.Д. Симонович розробив схему серогрупування фітопатогенних бактерій роду Pseudomonas, яка використовується і зараз. Однак сьогоднішнє використання цієї схеми серогрупування ускладнюється відсутністю всіх даних, накопичених за роки її застосування. Крім того, схема не відповідає сучасній систематиці фітопатогенних бактерій роду Pseudomonas. Цілься. На основі власних експериментальних результатів та даних наукової літератури провести модернізацію схеми серогрупування фітопатогенних бактерій роду Pseudomonas. методи. У роботі досліджено штами патоварів Pseudomonas syringae atrofaciens, coronafaciens, tabaci, які виділені з рослин пшениці, жита, вівса, тютюну та різних видів уражених бур’янів у різних регіонах України. Антигенні властивості штамів бактерій вивчали за допомогою реакцій аглютинації та преципітації (методи подвійної імунодифузії Оухтерлоні) з використанням антисироваток до штамів P. syringae дев’яти серологічних груп (I, II, III, IV, V, VI, VII, VIII, IX). Для проведення реакції преципітації О- та ОН-антигени отримували модифікованим методом Грасса. Наявність такої ж кількості ліній преципітації досліджуваних антигенів, як і кількості ліній з гомологічною антисироваткою відповідної серогрупи, свідчила про приналежність їх до цієї серогрупи за відомою схемою серогрупування фітопатогенних бактерій, розробленою в 1979 р. Л.Т. Пастушенко та І.Д. Симоновича. Результати. Доведено, що штами патоварів P. syringae, виділені з різних злаків (жито, пшениця, овес) і сегетальної рослинності, відрізняються за антигенним складом. Антигенний склад штамів P. syringae залежить від рослини-господаря, з якої був виділений збудник. Штами збудника базальної лускоподібної гнилі P. syringae pv. atrofaciens, виділені з пшениці, відносяться до чотирьох серологічних груп (II, IV, V, VI), з жита - до п'яти серологічних груп (I, II, IV, V, VI), а також штами цього збудника, виділені з сегетальної рослинності агрофітоценоз пшениці. Штами Halo Bligth P. syringae pv. coronafaciens з уражених рослин вівса належать до двох серологічних груп (I, V). Схема серогрупування доповнена новими даними про антигенні властивості P. syringae pv. томат, збудник бактеріальної плямистості томатів (Solanum lycopersicum), яка відноситься до IV серогрупи. Встановлено, що P. syringae pv. штами tabaci, що викликають лісову пожежу тютюну, входять до складу трьох серогруп - VII, VIII, IX, а не двох, як було представлено на відомій схемі (1979). Висновки. Тому на основі власних досліджень і літературних даних розроблена Л.Т. Пастушенко та І.Д. Симоновича модернізовано. В оновленій схемі присутні сучасні видові назви фітопатогенів, ця схема вносить нову інформацію про серогрупи P. syringae pv. atrofaciens виділено з насіння і рослин жита, бур'янів, P. syringae pv. coronafaciens - з рослин вівса, P. syringae pv. tabaci - з тютюну, і P. syringae pv. томат - від уражених рослин томатів.
Keywords: Pseudomonas syringae pv.; аглютинація; agglutination; преципітація; precipitation; серогрупування; serogrouping; кафедра біотехнології і мікробіології